ECONOMIC EFFICIENCY OF THE INTRODUCTION OF AUTOMATED PRE-TRIP INSPECTION SYSTEMS AT THE WORKPLACES OF THE BELARUSIAN RAILWAY - Макеев, Вячеслав Валерьевич; Рыбина, Татьяна Михайловна (Medicine in Kuzbass, 2025)
Purpose of the work is to study the economic efficiency in the implementation of automated pre–shift inspection systems (hereinafter referred to as AFS) at the workplaces of the Belarusian Railway.Materials and methods. The data on temporary disability of employees of the Belarusian Railway (hereinafter – BR) for the three-year period from 2017 to 2019 (the period before the COVID-19 pandemic) were used. Calculations of the economic efficiency of the introduction of automated pre-shift inspection systems in the conditions of the Belarusian Railways have been performed.Results. Analyzes the factors determining the economic efficiency of automated pre-shift examination systems: reducing the number of days with temporary disability, reducing the cost of training a new employee (replenishing staff), reducing the risk of emergencies, increasing the productivity of a medical worker due to the possibility of examining several employees simultaneously, and calculating the cost of implementing AFS. A methodology for calculating the economic efficiency of implementing AFS for railway enterprises is proposed. The calculation is based on the example of BR data.Conclusion. The calculations performed to determine economic efficiency have shown that the use of AFS is economically feasible for implementation in Belarusian Railways, and the payback period does not exceed 1 year. The proposed methodology can be recommended for transport companies when analyzing the possibility of implementing AFS during pre-shift (pre-trip) inspections.
Keywords: pre-shift inspection; economic efficiency; risk